How does elevated grassland productivity influence populations of root hemiparasites? Commentary on Borowicz and Armstrong (Oecologia 2012) - Těšitel, Jakub; Hejcman, Michal; Lepš, Jan; Cameron, Duncan D (Oecologia, 2013)
In their recent study, Borowicz and Armstrong (Oecologia 169:783-792, 2012) investigated effects of nutrient availability and competition for light on a perennial root hemiparasite Pedicularis canadensis. Their study showed a reduction of community productivity as a result of hemiparasite infection independently of a clear positive effect of increased nutrients. In contrast, there was a minimal effect of increased competition for light on growth of the parasite. Here, we summarize the available data on the influence of nutrient availability (closely related to productivity) on temperate grassland root hemiparasites thus expanding the discussion presented by Borowicz and Armstrong (Oecologia 169:783-792, 2012). Most studies show that root hemiparasites are highly sensitive to elevated competition for light in productive environments, which is manifested as an increase in mortality coupled to a decrease in population density. Such responses reflect increased mortality of hemiparasite seedlings that are physiologically inefficient in terms of photosynthesis and nutrient acquisition owing to a limited root network and consequently, are highly sensitive to competition for light. However, the susceptibility of hemiparasites to competition for light tends to decrease for individuals that survive the critical seedling stage. Moreover, survivors benefit from elevated nutrient availability, resulting in increased growth and fecundity. Elevated productivity can thus have opposing effects on the survival and growth of hemiparasites depending on life stage. We conclude that the findings by Borowicz and Armstrong (Oecologia 169:783-792, 2012) are not in conflict with this general view that root hemiparasite population ecology is strongly influenced by competition for light in highly productive environments.
Keywords: Poaceae; Host-Parasite Interactions; Andropogon; interakce hostitele a parazita; Pedicularis; lipnicovité; ekosystém; Ecosystem